Structural organization and pattern of innervations of human Meissner’s corpuscle: a light microscopic study - Bhat, Gh. Mohd.; Shah, Naseer Ahmad; Itoo, Mohd. Saleem; Shah, Bashir Ahmad; Shahdad, Shaheen; Khan, Javeed Ahmad (International Journal of Research in Medical Sciences, 2017)
Background: Human glabrous skin has very rich nerve supply in the form of specialized nerve endings like Meissner’s corpuscles, Pacinian corpuscles, Krause end bulbs etc for carrying sensory information to brain. Aim of study: To study the structure, pattern of innervations and nerve terminations of human Meissner’s corpuscle. Methods: Skin samples from sixty human beings (age range 2 to 72 years) were taken, sections prepared and stained with a cytological (Haematoxylin – Eosin and Vongieson’s stains) and a neural stain (Silver Impregnation). Results: With cytological stain, Meissner’s corpuscles were seen in dermal papillae of glabrous skin, each consisting of a cellular structure having a peripheral capsule and central core of transversely arranged cells. With neural stain, each corpuscle was seen to be oval, globular or cylindrical structure, having a capsule surrounding the core of spirally arranged nerve fibers, sandwiched by Schwann cells. In between nerve fibers of the core were seen small bundles of collagen fibers. 2-6 nerve fibers innervated each Mc from the sub corial plexus of nerves and formed various patterns of nerve endings like networks, end bulbs and varicosities inside the Meissner’s corpuscle. Conclusion: Meissner’s corpuscle is a complex structure composed of capsule - consisting of spindle shaped capsular cells interspersed in collagen fibers, surrounding a core of helically arranged nerve fibers, Schwann cells and collagen fibers.